Electronic reservation for hotel services / Zazaleena Zakariah - Zakariah, Zazaleena (2005)
In the twenty-first century, the main factors affecting hotel services success are globalization, technological developments, and changes in customers' preferences, differences in competition among hotels, horizontal and vertical integration and legal applications. Responding to the phenomena, electronic reservations for hotel services have been introduced and widely implemented throughout the world. The main purposes of electronic reservations services include transferring a portion of the accommodation agency sales, rife with commissions and segment reservations fees, to direct reservations channels. Through electronic reservations services, customer services are enhanced, information is personalized and other accommodation information is integrated. In Malaysia, the growth of electronic reservations services have been enormous over the last few years as the service offers many advantages to the involved parties especially customers and retailers. Responding to the phenomena, this study was conducted to gain deeper understanding regarding the service. The study comprised of customers side, retailers side and web observation. Through the study, customers and retailers perception towards electronic reservation are gathered and analyzed using eleven dimensions of electronic service quality. Besides that, customers and retailers suggestions and recommendations in enhancing the service quality are also identified. Furthermore, web observations are carried out to assess the state of electronic reservation service using 42 features of E-CRM. From the study results, a framework of electronic reservation for hotel services is developed.